Hip Function 6 to 10 Months After Arthroscopic Surgery: A Cross-sectional Comparison of Subjective and Objective Hip Function, Including Performance-Based Measures, in Patients Versus Controls. Issue 6 (4th June 2019) - Wörner, Tobias; Nilsson, Johanna; Thorborg, Kristian; Granlund, Viktor; Stålman, Anders; Eek, Frida
Background: Little is known about hip-related function, mobility, and performance in patients after hip arthroscopic surgery (HA) during the time that return to sports can be expected. Purpose: To evaluate measures of subjective and objective hip function 6 to 10 months after HA in patients compared with healthy controls and to compare objective function in the HA group between the operated and nonoperated hips. Study Design: Cross-sectional study; Level of evidence, 3. Methods: A total of 33 patients who had undergone HA (mean, 8.1 ± 2.6 months postoperatively) and 33 healthy participants matched on sex, age, and activity level were compared regarding subjective hip function (Copenhagen Hip and Groin Outcome Score [HAGOS]) and objective function including hip range of motion (ROM; flexion, internal rotation, and external rotation), isometric hip muscle strength (adduction, abduction, flexion, internal rotation, and external rotation), and performance-based measures: the Y Balance Test (YBT), medial and lateral triple-hop test, and Illinois agility test. Group differences were analyzed using independent-samples t tests. Paired-samples t tests were used for a comparison of the operated and nonoperated hips. Standard effect sizes (Cohen d ) were provided for all outcomes. Results: The HA group reported worse subjective hip function than the control group (HAGOS subscores: d = –0.7 to –2.1; P ≤ .004). Objective measures of hip ROM ( d = –0.5 to –1.1; P ≤ .048), hip flexion strength ( d = –0.5; P = .043), and posteromedial reach of the YBT ( d = –0.5; P = .043) were also reduced in the HA group, although there were no significant differences between groups regarding the remaining objective measures ( d = –0.1 to –0.4; P ≥ .102 to .534). The only significant difference between the operated and nonoperated hips in the HA group was reduced passive hip flexion ( d = –0.4; P = .045). Conclusion: Patients who had undergone HA demonstrated reduced subjective hip function compared with controls 6 to 10 months after surgery, when return to sports can be expected. While most objective strength and performance test results were comparable between the HA and control groups at 6 to 10 months after surgery, the HA group presented with impairments related to hip mobility and hip flexion strength. No consistent pattern of impairments was found in operated hips compared with nonoperated hips.